(3GdcGed aj GddZIs - (3eMeO Hf jRjO Hf YHO GdCcHQ GdKeGdj GdCROj, GdeHQO , CHh GdYHGS,J (B286 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg GdeJajgbhf bhdg Udi Gddg Ydjg hSde GdehWFhf CcfGakG eKd hMbjbI s
(3BNQgG (B:s
(3bGdhba jNQLhf GdQShd hEjGce Ci jNQLhfce dCf JDefhG HGddg QHce Je gPG GdcJGH GdcGed hGdTcQ ddg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B144 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B114s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs